Development of a novel tissue expander for non-keratinised epithelial tissue - Wilson, Lucy May (2023)
Cloacal malformations represent one of the most complex forms of paediatric anorectal malformations (ARM). With an incidence of 1 in 50,000 live births, ARMs are rare but have a significant impact on patients’ quality of life as they reach puberty and beyond. Surgical intervention is the only treatment option, with the main goals to separate the drainage of faecal and urinary streams, protect renal function, repair the vagina and preserve internal genitalia, allowing patients to become sexually active in the future. The standard practice of surgical intervention can be very invasive for some patients, increasing the morbidity of the procedure. A minimally invasive cloaca repair operation (MICRO) may reduce any additional surgical morbidity. Implanted tissue expanders are preferable to tissue scaffolds or implants as they avoid complications associated with rejection and expansion of native tissue is preferable to implant of tissue from other bodily sites. Characterisation of the vagina of female pigs (Canberra 12 strain; Landrace/large white/duroc) aged 6 weeks to 6 months has confirmed the suitability of a porcine model for cloacal malformations in paediatric patients. The macroscopic anatomy of female pigs at 8 weeks of age has comparable anatomy to that of children with ARM at an operative age of 6-18 months. Investigations of histology and 3D morphology are also similar, in comparison with human paediatric images. Both species have undifferentiated mesenchyme below the stratified epithelium, with widespread vascular and neural supply to the organ. An in-house, isotropic self-inflating hydrogel expander has been developed. The hydrogel is comprised of co-polymers; poly (lactic acid), poly (ethyleneglycol 600) diacrylate, acrylic acid, hydroxyethyl acrylate and bis(2,4,6-trimethylbenzoyl)-phenylphosphineoxide, annealed under ultraviolet light for a specified time period. In vitro implantation of the developed hydrogel tissue expanders within porcine vaginal tissue and the conduction of in vitro swelling tests within organ baths has provided vital data for future porcine in vivo expansion trials. The ability for porcine vaginal tissue to withstand the pressure of intraluminal expansion in suboptimal conditions (i.e., within an organ bath) has also been explored. The results suggest that the progression of this work into in vivo implantation trials should produce promising results. Future in vivo studies would involve the placement of the developed tissue expanders in the vagina of the porcine models and will, ideally, create tissue with the same histological, hormonal, and physiological properties as the native tissue. The newly expanded tissue would then benefit from the resident innervation and blood supply, potentially allowing future patients to experience a better functionality immediately and later in life when reproductive activity commences.